Manufacturing of die blanks from hard alloy granulated mixture and influence of chemical composition of the mixture on technological properties of hard alloy die blanks - O. Yu. Khodosovskaya; L. V. Ovsyanikova; T. V. Gapeenko (Литьë и металлургия, 2024)
The technology of manufacturing dies from a hard alloy granulated mixture includes the following operations: preparation of raw materials, forming of blanks, and subsequent sintering. The preparation of hard alloy mixtures consisting of carbide powders and binder metals is one of the main operations in the production of hard alloys. The properties of the resulting alloys largely depend on the conditions of performing this operation. All operations are interconnected, and any change in technological parameters can lead to a change in the formation of the final material structure and, consequently, its properties. This article discusses the technology of manufacturing and the production process of die blanks from a hard alloy granulated mixture. The results of laboratory studies of the hard alloy mixture, the manufacture, and production tests of die blanks are described.